1982
DOI: 10.1136/hrt.48.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and hormonal effects of captopril in primary pulmonary hypertension.

Abstract: SUMMARY The treatment of primary pulmonary hypertension is unsatisfactory. Since, in animals, experimental pulmonary vasoconstriction may be mediated in part by angiotensin II, we treated five primary pulmonary hypertensive patients with captopril for four days. To ensure accuracy of haemodynamic and hormone data, the patients were studied under conditions of constant body posture, regulated dietary sodium and potassium intake, and unchanged diuretic therapy. Captopril reduced mean pulmonary arterial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…7 Two smaller case series have reported decreased pulmonary vascular resistance and improved RV function with captopril treatment in patients with RHF due to PAH. 36,37 Studies with patients with RHF due to an RV supporting the systemic circulation have reported no or only minor beneficial effect of treatment with ACE inhibitors or ARBs. 38,39 These contrasting results may reflect the issue of pulmonary versus cardiac effects of RAAS-blocking treatments.…”
Section: Effects Of Losartan Treatmentmentioning
confidence: 99%
“…7 Two smaller case series have reported decreased pulmonary vascular resistance and improved RV function with captopril treatment in patients with RHF due to PAH. 36,37 Studies with patients with RHF due to an RV supporting the systemic circulation have reported no or only minor beneficial effect of treatment with ACE inhibitors or ARBs. 38,39 These contrasting results may reflect the issue of pulmonary versus cardiac effects of RAAS-blocking treatments.…”
Section: Effects Of Losartan Treatmentmentioning
confidence: 99%
“…In this regard, clinical trials have been disappointing, both in their inconsistent results and in their methodology. Studies with ACE inhibitors in PPH have produced conflicting results in terms of pulmonary haemodynamic benefit [9,[25][26][27] and consequently these agents have not found a place in the treatment of these patients. In cor pulmonale, acute dosing studies have demonstrated variable effects on pulmonary haemodynamics [28][29][30][31][32][33] whereas chronic dosing studies have been short-term and have included only small numbers of patients [34,35] ( Table 1).…”
Section: Therapeutic Correlatesmentioning
confidence: 99%
“…In the 1980s, four small case-series (26 patients in total) reported on the haemodynamic effects of captopril in PAH. Three of the studies were positive and found a significant increase in cardiac output [60,61] and exercise capacity [62]. One study, however, did not observe any haemodynamic changes, neither positive nor negative [63].…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%